Evaluation of Hepatic Encephalopathy Triggers and Outcomes in Chronic Liver Disease: A Regional Perspective - Mashooque Ali Samejo; Osama Ahmed; Muhammad Arsalan; Adil Hassan; Rehmat Ullah Bhatti; Ubedullah Bughio; Ehsan Ul Haq (Pakistan Journal of Medicine and Dentistry)
Background: Chronic liver disease (CLD) accounts for a neuropsychiatric complication called hepatic encephalopathy (HE). This study aimed to explore the key precipitating factors in HE and determine how they correlated with disease severity; findings were compared to global trends.